Malaysia's industrialization : - Ali, Anuwar (Oxford University Press, 1992)
Until recently Malaysia has been dependent on technology transfer through direct foreign investment. In 1986 the Industrial Master Plan was passed. This work examines the objectives of this Plan which highlights the fact that future industrial development must be propelled by domestic technological capabilities. The book also explores strategic options for public and private interaction in development.